Living More Than Just Enough for the City: Persistence of High-Quality Vegetation in Natural Areas in an Urban Setting - Marcia E. Moore; Jessica D. Stephens; Rebecca W. Dolan (Diversity, 2011)
Urban environments pose special challenges to flora, including altered disturbance regimes, habitat fragmentation, and increased opportunity for invasion by non-native species. In addition, urban natural area represents most people’s contact with nature, given the majority of the world’s population currently live in cities. We used coefficients of conservatism (C-values), a system that ranks species based on perceived fidelity to remnant native plant communities that retain ecological integrity, to quantify habitat quality of 14 sites covering 850 ha within the city of Indianapolis, Indiana, in the Midwestern United States. All sites contained significant natural area and were inventoried via intensive complete censuses throughout one or two growing seasons within the last 15 years. Mean C-values for five sites were high, especially when compared to values reported for the highest quality preserves in central Indiana. However, for most sites the difference in mean C-value with and without non-natives was rather high, meaning that natural quality is likely to have been compromised by the presence of non-natives. Sites receiving the highest levels of stewardship and those with the least public access via trails had the highest mean native C-values. A total of 34 invasive non-native species were found across all 14 sites. Most were woody species. Mean C-value over all sites was significantly negatively correlated with the number of non-natives present, especially those considered invasive. These results demonstrate for the Indianapolis area, and likely other urbanized Midwestern cities, remnant natural areas can retain high ecological value, especially if they receive regular environmental stewardship.